Video Conferencing in Distance Learning: A New Zealand Schools’ Perspective - Rachel Roberts (Journal of Open, Flexible and Distance Learning, 2011)
This article sets outs to trace the development of video conferencing in distance learning in the New Zealand secondary school sector. It begins with an overview of the definition and development of distance learning; then traces the technology of video conferencing from its inception to the present day. It goes on to look at the growth of video conferencing and the role and contribution it has made to distance learning in New Zealand schools, and concludes with a brief discussion of possible future directions.